Medical Equipment Inventory Information System in Public Hospitals - Dani Dani (Komunitas Dosen Indonesia, 2026)
General Hospitals (RSU) require an effective medical equipment inventory management system to support improved healthcare quality. Currently, many hospitals still use manual methods for recording and managing inventory, which often leads to various challenges such as data errors, lost equipment, distribution delays, and difficulties in monitoring the condition and availability of medical equipment. This study aims to design and implement a web-based Medical Equipment Inventory Information System (SIIAM) to improve the efficiency, accuracy, and transparency of hospital inventory management. To address these issues, a web-based Medical Equipment Inventory Information System (SIIAM) was developed, designed to assist hospitals in managing inventory data in an integrated, fast, and accurate manner. The system was developed using the Waterfall method, which includes requirement analysis, system design, implementation, testing, and maintenance, and was evaluated through system testing to measure its effectiveness. SIIAM can record real-time data on the procurement, maintenance, and use of medical equipment. Furthermore, this system can help identify equipment needs, organize periodic maintenance schedules, and generate reports required by hospital management. Based on testing results, implementing SIIAM increased the efficiency of medical equipment inventory management by up to 30%. It reduced the recording error rate by 20%, while providing real-time access to integrated data across hospital units. Therefore, the web-based SIIAM is an effective solution for enhancing efficiency, accuracy, and transparency in medical equipment inventory management, thereby improving healthcare service quality and patient safety in General Hospitals.